Cortical Thickness in Dutch Police Officers: An Examination of Factors Associated with Resilience. Issue 2 (11th March 2020) - Setroikromo, Santoucha N.W.; Bauduin, Stephanie E.E.C.; Reesen, Joyce E.; van der Werff, Steven J.A.; Smit, Annika S.; Vermetten, Eric; van der Wee, Nic. J.A.
Abstract: Previous neuroimaging studies on resilience have generally compared resilience and psychopathology after stress exposure, which does not allow for conclusions regarding correlates specific to resilience. The aim of the present study was to investigate resilience‐specific correlates in cortical thickness and/or cortical surface area and their correlations with psychometric measurements, using a three‐group design that included a non–trauma‐exposed control group in order to disentangle effects related to resilience from those related to psychopathology. Structural magnetic resonance imaging scans were acquired from 82 Dutch police officers. Participants were categorized into resilient ( n = 31; trauma exposure, no psychopathology), vulnerable ( n = 32; trauma exposure, psychopathology), and control groups ( n = 19; no trauma exposure, no psychopathology). Specific regions of interest (ROIs) were identified based on previous studies that found the rostral and caudal anterior cingulate cortex (ACC) to be implicated in trauma‐related psychopathology. Cortical thickness and surface area of the ROIs—the rostral and caudal ACC—and of the whole brain were examined. No significant differences in cortical thickness or surface area were found between the resilient group and other groups in the ROI and whole‐brain analyses. Thus, the results of the present study provide no evidence of an association between resilience to traumatic stress and measures of thickness and surface area in cortical regions of the brain in a sample of Dutch police officers. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Espesor cortical en agentes de policía holandeses: un examen de los factores asociados con la resiliencia ESPESOR CORTICAL EN POLICÍAS HOLANDESES RESILIENTES Los estudios previos de neuroimagen sobre la resiliencia generalmente han comparado la resiliencia y la psicopatología después de la exposición al estrés, lo que no permite sacar conclusiones sobre correlatos específicos de la resiliencia. El objetivo del presente estudio fue investigar los correlatos específicos de la resiliencia en el grosor cortical y/o el área de la superficie cortical y sus correlaciones con las mediciones psicométricas, utilizando un diseño de tres grupos que incluyó un grupo de control no expuesto al trauma para desenredar los efectos. relacionados con la resiliencia de los relacionados con la psicopatología. Se adquirieron imágenes de resonancia magnética estructural de 82 agentes de policía holandeses. Los participantes se clasificaron en grupos resilientes ( n = 31; exposición al trauma, sin psicopatología), vulnerables ( n = 32; exposición al trauma, con psicopatología) y grupo de control ( n = 19; sin exposición al trauma, sin psicopatología). Se identificaron regiones de interés específicas (ROI en su sigla en inglés) en base a estudios previos, que encontraron que el ACC rostral y caudal está implicado en la psicopatología relacionada con el trauma. Se examinaron el grosor cortical y el área de la superficie de las ROI, la corteza cingulada anterior rostral y caudal (ACC en su sigla en inglés), y de todo el cerebro. No se encontraron diferencias significativas en el grosor cortical o el área de superficie entre los resilientes y los otros grupos en los análisis de ROI y de todo el cerebro. Por lo tanto, los resultados del presente estudio no proporcionan evidencia de una asociación entre la resiliencia al estrés traumático y las medidas de espesor y área de superficie en las regiones corticales del cerebro en una muestra de policías holandeses. 抽象: 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 JOTS‐19‐0001.R2 Setroikromo Cortical thickness in resilient Dutch police officers Traditional Chinese 標題: 具恢復力的荷蘭警員其大腦皮質厚度 撮要: 過往有關恢復力的腦神經成像研究, 一般比較樣本承受壓力後的恢復力和精神病理學, 無法找出特殊地跟恢復力有關的關連因素。本研究旨在透過檢視大腦皮質厚度和/或皮質表面面積, 探查特殊地跟恢復力有關的關連因素, 以及它們跟心理測量數據的關係。我們採用三組別設計, 包含無受創的對照組, 以分辨跟恢復力相關和跟心理疾病相關的效應。我們取得82名荷蘭警察的結構性磁力共振成像。樣本劃分為恢復力組 (n = 31; 受創, 無心理疾病)、脆弱組 (n = 32; 受創, 有心理疾病), 及對照組(n = 19; 無受創, 無心理疾病)。我們基於過往研究辦識出感興趣區域(ROIs), 即創傷相關的心理疾病對前扣帶皮層(ACC) 吻端及尾端的影響, 並檢視ROIs的皮質厚度、表面面積 (即ACC的吻端及尾端) 及整個腦部。在ROI和腦部整體的分析中, 均無發現恢復力組別與其他組別在皮質厚度或表面面積方面有顯著差異。因此, 本研究使用的荷蘭警察樣本, 並未能提供證據反映面對創傷壓力的恢復力跟大腦皮質區域的厚度及表面面積測量有所關連。 Simplified Chinese 标题: 具恢复力的荷兰警员其大脑皮质厚度 撮要: 过往有关恢复力的脑神经成像研究, 一般比较样本承受压力后的恢复力和精神病理学, 无法找出特殊地跟恢复力有关的关连因素。本研究旨在透过检视大脑皮质厚度和/或皮质表面面积, 探查特殊地跟恢复力有关的关连因素, 以及它们跟心理测量数据的关系。我们采用三组别设计, 包含无受创的对照组, 以分辨跟恢复力相关和跟心理疾病相关的效应。我们取得82名荷兰警察的结构性磁力共振成像。样本划分为恢复力组 (n = 31; 受创, 无心理疾病)、脆弱组 (n = 32; 受创, 有心理疾病), 及对照组(n = 19; 无受创, 无心理疾病)。我们基于过往研究办识出感兴趣区域(ROIs), 即创伤相关的心理疾病对前扣带皮层(ACC) 吻端及尾端的影响, 并检视ROIs的皮质厚度、表面面积 (即ACC的吻端及尾端) 及整个脑部。在ROI和脑部整体的分析中, 均无发现恢复力组别与其他组别在皮质厚度或表面面积方面有显著差异。因此, 本研究使用的荷兰警察样本, 并未能提供证据反映面对创伤压力的恢复力跟大脑皮质区域的厚度及表面面积测量有所关连。